Neodymium-doped quartz glass with fluorescence spectrum blue shift to 870nm wave band and preparation method of neodymium-doped quartz glass
By co-doping phosphorus elements in quartz glass and regulating the local structure of Nd ions, the fluorescence peak of neodymium-doped quartz glass was successfully moved from 900nm blue to 870nm, solving the problem of insufficient pumping efficiency and output stability in the 870nm band laser emission, and expanding its application potential in the fields of biological imaging, quantum communication and high-power lasers.
Patent Information
- Application Number
- CN202411942651.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-27
AI Technical Summary
Existing Nd-doped fiber lasers face technical bottlenecks in pumping efficiency and laser output stability in laser emission in the 870nm band.
By co-doping phosphorus elements, the local microstructure of Nd ions in quartz glass is accurately regulated, and its coordination environment is optimized, thereby enhancing the coordination field, and promoting the energy level distribution of Nd ions to change. The fluorescence peak of neodymium-doped quartz glass is successfully moved from 900nm blue to 870nm.
It effectively breaks through the limitations of the 900nm band application, provides technical support for the application of the 870nm band in the fields of biological imaging, quantum communication and precision measurement, and expands the application prospects of Nd doped quartz glass in high-power lasers and cutting-edge photonics.
Smart Images

Figure CN119707279A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of quartz glass optical fiber, and in particular to a neodymium-doped quartz glass with a fluorescence spectrum blue-shifted to a 870nm band and a preparation method thereof. Background Art
[0002] Neodymium (Nd)-doped materials have excellent optical properties such as low pumping threshold and high emission cross section due to their unique energy level structure and rich absorption bands, and have become the core active ions in 1μm band high-power laser devices and industrial applications. In recent years, the application of Nd-doped materials in the 900nm band has gradually attracted attention. This band is not only suitable as an efficient pump source for Yb-doped materials, but also located in the atmospheric transmission window, which reduces the absorption loss of light in the air. Therefore, it shows significant potential in the fields of atmospheric detection, differential absorption radar and quantum communication. In addition, in the field of biological imaging, 900nm band lasers can excite a variety of fluorescent proteins, have a certain tissue penetration depth, and enhance imaging effects. However, Nd-doped materials in the 900nm band still have shortcomings in terms of tissue penetration depth, imaging resolution and signal transmission stability in biological imaging and fiber-optic communications.
[0003] With the increasing demand for high resolution in biological imaging and the strict requirements for low attenuation in fiber-optic communications, the application potential of the 870nm band is gradually emerging. Compared with the 900nm band, the 870nm band is closer to the ideal range of the biological optical window, which can significantly improve the penetration depth of biological tissues and imaging resolution, while significantly reducing the signal attenuation rate in fiber-optic transmission. Therefore, it is regarded as an ideal choice for biological imaging, quantum communication, and atmospheric detection. However, the realization of laser emission in the 870nm band in Nd-doped fiber lasers still faces technical bottlenecks, especially limitations in pump efficiency and laser output stability. Summary of the invention
[0004] Aiming at the technical bottlenecks currently faced in realizing laser emission in the 870nm band in Nd-doped fiber lasers, especially the limitations in pumping efficiency and laser output stability, the present invention provides a neodymium-doped quartz glass with a fluorescence spectrum blue-shifted to the 870nm band and a preparation method thereof.
[0005] The present invention discloses a method for preparing Nd-doped quartz glass with a fluorescence spectrum blue-shifted to 870 nm. The components of the Nd-doped quartz glass include P2O5, Nd2O3 and SiO2. The preparation method includes the following steps: Step 1. Weigh the precursor raw materials of each component according to the selected molar percentage, the precursor raw material of P2O5 is phosphoric acid, the precursor raw material of Nd2O3 is neodymium chloride hexahydrate, 90wt% to 95wt% of the precursor raw material of SiO2 is porous silica powder, and 5wt% to 10wt% of the precursor raw material of SiO2 comes from silicon alkoxide; Step 2. Prepare a mixed solution according to the volume ratio of silicon alkoxide: water: organic solvent = 1:2~10:4~20, then add neodymium chloride hexahydrate and phosphoric acid to the mixed solution in sequence, then add silicon alkoxide hydrolysis catalyst to adjust the pH value of the solution to the first pH value, and stir well at room temperature for 1 to 20 hours to obtain Nd 3+ , P 5+ The co-doped silicon oxide transparent sol solution is then allowed to stand for 1 to 5 days; Step 3. Add the porous silica powder in batches according to a fixed addition amount to the vigorously stirred silica transparent sol solution for multiple times, and continue stirring for 2 to 48 hours after the addition is completed to form a suspension; Step 4. Granulate the suspension to obtain a preliminary powder, and heat the preliminary powder to 1000° C. in an oxygen atmosphere in a tube furnace and keep it at 1000° C. for 5 to 20 hours to remove residual carbon and hydroxyl groups to form Nd-doped high-phosphorus silica powder; Step 5. ball milling the silica powder using a ball mill and controlling the particle size to be below 100 μm; Step 6. Place the ball-milled silica powder in a graphite crucible and place in a high temperature furnace at 1500 to 1730°C for 10 -1 Up to 10 -3 The melting is carried out for 1 to 8 hours under a torr vacuum degree, and bubble-free transparent glass is formed along with furnace cooling. The bubble-free transparent glass is neodymium-doped quartz glass.
[0006] Preferably, the molar percentages of the components of the Nd-doped quartz glass are: P2O5: 1 mol% to 15 mol%, Nd2O3: 0.05 mol% to 0.8 mol%, and the remaining components are SiO2. Preferably, the median particle size of the porous silica powder is in the micro-nano order.
[0007] Preferably, the silicon alkoxide is Si(OC2H5)4 or Si(OCH3)4. When the silicon alkoxide is Si(OC2H5)4, the organic solvent is C2H5OH; when the silicon alkoxide is Si(OCH3)4, the organic solvent is CH3OH.
[0008] Preferably, the siliconate hydrolysis catalyst is hydrochloric acid or ammonia water. When the siliconate catalyst is hydrochloric acid, the first pH value is 1 to 3; when the siliconate catalyst is ammonia water, the first pH value is 8 to 10.
[0009] Preferably, in step 3, the fixed addition amount is 1 to 5 g each time.
[0010] Preferably, in step 4, the suspension is granulated by rotary evaporation.
[0011] Another aspect of the present invention is a neodymium-doped quartz glass with a fluorescence spectrum blue-shifted to the 870nm band, which is prepared by the above-mentioned method for preparing neodymium-doped quartz glass with a fluorescence spectrum blue-shifted to the 870nm band.
[0012] The third aspect of the present invention is a Nd-doped quartz optical fiber core rod, which is prepared from the above-mentioned Nd-doped quartz glass with a fluorescence spectrum blue-shifted to the 870nm band.
[0013] Preferably, the Nd-doped quartz glass is cold worked and polished to obtain an optical fiber core rod, the surface roughness of the optical fiber core rod is less than 10 nm, and the optical fiber core rod is placed in hydrofluoric acid with a mass concentration of 5 to 20% for acid treatment for 5 to 15 minutes, then taken out and dried to obtain the Nd-doped quartz optical fiber core rod.
[0014] Compared with the prior art, the neodymium-doped quartz glass of the present invention has a fluorescence spectrum blue-shifted to the 870nm band and a preparation method thereof, by co-doping phosphorus elements, precisely regulating the local microstructure of Nd ions in the quartz glass, optimizing its coordination environment, thereby enhancing the coordination field, causing the energy level distribution of Nd ions to change, and successfully blue-shifting the fluorescence peak of the neodymium-doped quartz glass from 900nm to 870nm, effectively breaking through the limitation of the application of the 900nm band, providing strong technical support for the application of the 870nm band in the fields of biological imaging, quantum communication near-infrared light source and precision measurement, and further expanding the application prospects of Nd-doped quartz glass in high-power lasers and cutting-edge photonics. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0016] Figure 1 The present invention is a schematic flow chart of a method for preparing neodymium-doped quartz glass with a fluorescence spectrum blue-shifted to the 870nm band.
[0017] Figure 2 This is the 2D-HYSCORE spectrum of the Nd-doped quartz glass in Example 1.
[0018] Figure 3This is the EPMA surface scanning image of the P element in the Nd-doped quartz glass in Example 2.
[0019] Figure 4 Schematic diagram of normalized absorption spectrum of Nd ions based on the absorption peak at 580nm at room temperature in the neodymium-doped quartz glass in comparative example 1 and example 2.
[0020] Figure 5 Schematic diagram of the normalized fluorescence spectrum (Ex=808nm) of the neodymium-doped quartz glass at room temperature in Comparative Example 1 and Example 2, with the fluorescence secondary peak near 900nm as the reference. DETAILED DESCRIPTION
[0021] In order to provide a further understanding of the purpose, structure, features, and functions of the present invention, the following detailed description is given in conjunction with the embodiments.
[0022] In the description of the present invention, it should be noted that the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside", etc. indicate directions or positional relationships based on the directions or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction. Therefore, they cannot be understood as limitations on the present invention.
[0023] See also Figure 1 The present invention provides a method for preparing a neodymium-doped quartz glass having a fluorescence spectrum blue-shifted to the 870 nm band, wherein the components of the neodymium-doped quartz glass include P2O5, Nd2O3 and SiO2, and the preparation method comprises the following steps: Step 1. Weigh the precursor raw materials of each component according to the selected molar percentage, the precursor raw material of P2O5 is phosphoric acid, the precursor raw material of Nd2O3 is neodymium chloride hexahydrate, 90wt% to 95wt% of the precursor raw material of SiO2 is porous silica powder, and 5wt% to 10wt% of the precursor raw material of SiO2 comes from silicon alkoxide; Step 2. Prepare a mixed solution according to the volume ratio of silicon alkoxide: water: organic solvent = 1:2~10:4~20, then add neodymium chloride hexahydrate and phosphoric acid to the mixed solution in sequence, then add silicon alkoxide hydrolysis catalyst to adjust the pH value of the solution to the first pH value, and stir well at room temperature for 1 to 20 hours to obtain Nd 3+ , P 5+ The co-doped silicon oxide transparent sol solution is then allowed to stand for 1 to 5 days; Step 3. Add the porous silica powder in batches according to a fixed addition amount to the vigorously stirred silica transparent sol solution for multiple times, and continue stirring for 2 to 48 hours after the addition is completed to form a suspension; Step 4. Granulate the suspension to obtain a preliminary powder, then heat the preliminary powder to 1000° C. in an oxygen atmosphere in a tube furnace and keep it at 1000° C. for 5 to 20 hours to remove residual carbon and hydroxyl groups to form Nd-doped high-phosphorus silica powder; Step 5. ball milling the silica powder using a ball mill and controlling the particle size to be below 100 μm; Step 6. Place the ball-milled silica powder in a graphite crucible and place in a high temperature furnace at 1500 to 1730°C for 10 -1 Up to 10 -3 The melting is carried out for 1 to 8 hours under a torr vacuum degree, and bubble-free transparent glass is formed along with furnace cooling. The bubble-free transparent glass is neodymium-doped quartz glass.
[0024] Preferably, the molar percentages of the components of the Nd-doped quartz glass are: P2O5: 1 mol% to 15 mol%, Nd2O3: 0.05 mol% to 0.8 mol%, and the remaining components are SiO2.
[0025] Preferably, the silicon alkoxide is Si(OC2H5)4 or Si(OCH3)4. When the silicon alkoxide is Si(OC2H5)4, the organic solvent is C2H5OH; when the silicon alkoxide is Si(OCH3)4, the organic solvent is CH3OH.
[0026] Preferably, the silicon alkoxide hydrolysis catalyst is hydrochloric acid or ammonia water. When the silicon alkoxide hydrolysis catalyst is hydrochloric acid, the first pH value is 1 to 3; when the silicon alkoxide hydrolysis catalyst is ammonia water, the first pH value is 8 to 10.
[0027] Preferably, in step 3, the fixed addition amount is 1 to 5 g each time.
[0028] Preferably, in step 4, the suspension is granulated by rotary evaporation.
[0029] Another aspect of the present invention is a neodymium-doped quartz glass with a fluorescence spectrum blue-shifted to the 870nm band, which is prepared by the above-mentioned method for preparing neodymium-doped quartz glass with a fluorescence spectrum blue-shifted to the 870nm band.
[0030] The third aspect of the present invention is a Nd-doped quartz optical fiber core rod, which is prepared from the above-mentioned Nd-doped quartz glass with a fluorescence spectrum blue-shifted to the 870nm band.
[0031] Preferably, the Nd-doped quartz glass is cold worked and polished to obtain an optical fiber core rod, the surface roughness of the optical fiber core rod is less than 10 nm, and the optical fiber core rod is placed in hydrofluoric acid with a mass concentration of 5 to 20% for acid treatment for 5 to 15 minutes, then taken out and dried to obtain the Nd-doped quartz optical fiber core rod.
[0032] In actual use, porous silica refers to an amorphous silica powder with a certain porosity and a median particle size in the micro-nano range. The powder includes but is not limited to that prepared by vapor deposition.
[0033] Table 1: Specific Nd-doped quartz glass components of 6 examples and 1 comparative example
[0034] Embodiment 1: The components of the neodymium-doped quartz glass of this embodiment are: 0.05mol% Nd2O3, 5mol% P2O5, 94.95mol% SiO2, and its preparation method comprises the following steps: Step 1. Weigh the precursor raw materials of each component according to the selected molar percentage, the precursor raw material of P2O5 is phosphoric acid, the precursor raw material of Nd2O3 is neodymium chloride hexahydrate, 90wt% of the precursor raw material of SiO2 is porous silica powder, and 10wt% of the precursor raw material of SiO2 comes from silicon alkoxide; Step 2. Prepare a mixed solution in a volume ratio of silicon alkoxide: water: organic solvent = 1:6:12, wherein silicon alkoxide is Si(OC2H5)4 and organic solvent is C2H5OH. Add neodymium chloride hexahydrate and phosphoric acid to the mixed solution in sequence and stir thoroughly. Then, add silicon alkoxide hydrolysis catalyst HCl and adjust the pH value of the solution to a first pH value of 3. Stir thoroughly at room temperature for 10 hours to obtain Nd 3+ , P 5+ The co-doped silicon oxide transparent sol solution was allowed to stand for another 3 days; Step 3. Add the porous silica powder in batches at a fixed amount of 3 g each time to the vigorously stirred silica transparent sol solution, and continue stirring for 30 hours after the addition is completed to form a suspension; Step 4. Granulate the suspension by rotary evaporation to obtain a preliminary powder containing a certain amount of water and organic matter. Subsequently, place the preliminary powder in a tube furnace, slowly increase the temperature from 50°C to 1000°C at a rate of 1°C per minute in an oxygen atmosphere, and keep it at 1000°C for 10 hours to remove residual carbon and hydroxyl groups to form Nd-doped high-P silica powder; Step 5. Use a ball mill to ball mill the silica powder to control the particle size to be less than 100 μm; Step 6: Place the ball-milled silica powder in a graphite crucible and place it in a high-temperature furnace at 1730°C for 10 -3 Melting is carried out for 4 hours under a torr vacuum, and bubble-free transparent glass is formed as the furnace cools; Step 7. Cold process and polish the bubble-free transparent glass into 2 mm thick Nd-doped quartz sheet glass for optical and spectral performance testing and evaluation.
[0035] Test method: Grind 2mm thick Nd-doped quartz glass flakes into micron-sized glass powder, take 50mg powder sample, and perform four-pulse two-dimensional hyperfine sublevel correlation spectroscopy (2D-HYSCORE) test at 4K using E580 pulsed electron paramagnetic resonance (EPR) detector from Bruker, Switzerland.
[0036] Under 350mT magnetic field, Figure 2 It can be seen that the resonance peak at 6.0 is closely related to the magnetic core 31 The Larmor frequency of P (NA=100%, I=1 / 2) corresponds to that of Nd ions, indicating that most of the Nd ions exist in the local microstructure of the P element.
[0037] Embodiment 2: The components of the neodymium-doped quartz glass of this embodiment are: 0.1 mol% Nd2O3, 8 mol% P2O5, 91.9 mol% SiO2, and its preparation method comprises the following steps: Step 1. Weigh the precursor raw materials of each component according to the selected molar percentage, the precursor raw material of P2O5 is phosphoric acid, the precursor raw material of Nd2O3 is neodymium chloride hexahydrate, the precursor raw material of 95wt% of SiO2 is porous silica powder, and the precursor raw material of 5wt% of SiO2 comes from silicon alkoxide; Step 2. Prepare a mixed solution in a volume ratio of silicon alkoxide: water: organic solvent = 1:5:15, wherein silicon alkoxide is Si(OC2H5)4 and organic solvent is C2H5OH. Add neodymium chloride hexahydrate and phosphoric acid to the mixed solution in sequence and stir thoroughly. Then, add HCl, a silicon alkoxide hydrolysis catalyst, and adjust the pH value of the solution to a first pH value of 3. After stirring thoroughly at room temperature for 10 hours, Nd 3+ , P 5+ The co-doped silicon oxide transparent sol solution was allowed to stand for another 3 days; Step 3. Add the porous silica powder in batches in a fixed amount of 5 g each time to the vigorously stirred silica transparent sol solution, and continue stirring for 40 hours after the addition is completed to form a suspension; Step 4. Granulate the suspension by rotary evaporation to obtain a preliminary powder containing a certain amount of water and organic matter. Subsequently, place the preliminary powder in a tube furnace, slowly increase the temperature from 50°C to 1000°C at a rate of 1°C per minute in an oxygen atmosphere, and keep it at 1000°C for 8 hours to remove residual carbon and hydroxyl groups to form Nd-doped high-P silica powder; Step 5. Use a ball mill to ball mill the silica powder to control the particle size to be less than 100 μm; Step 6. Place the ball-milled silica powder in a graphite crucible and place it in a high-temperature furnace at 1700°C for 10 -3Melting is carried out for 4 hours under a torr vacuum, and bubble-free transparent glass is formed as the furnace cools; Step 7. Cold-process and polish the bubble-free transparent glass into a 2 mm sheet or an optical fiber core rod. The sheet glass is used for optical and spectral performance test and evaluation. The core rod is optically polished with a surface roughness of less than 10 nm. It is placed in HF acid with a mass concentration of 15% for acid treatment for 10 min, then taken out and dried for use as the core rod of Nd-doped high-P quartz optical fiber.
[0038] Figure 3 This is the EPMA surface scanning image of the P element in the Nd-doped quartz glass in Example 2, with a scanning step length of 50 μm. Figure 3 It can be seen that the P element in the Nd-doped quartz glass is distributed very evenly.
[0039] Comparative Example 1: The neodymium-doped quartz glass of this embodiment comprises: 0.8 mol% Nd2O3, 5 mol% Al2O3, 94.2 mol% SiO2, and its preparation method comprises the following steps: Step 1. Weigh the oxide precursor raw materials of each component according to the selected molar percentage, the precursor raw material of Nd2O3 is neodymium chloride hexahydrate, the precursor raw material of Al2O3 is aluminum chloride hexahydrate, 95wt% of the precursor raw material of SiO2 is porous silica powder, and 5wt% of the precursor raw material of SiO2 comes from silicon alkoxide; Step 2. Prepare a mixed solution in a volume ratio of silicon alkoxide: water: organic solvent = 1:10:20, wherein silicon alkoxide is Si(OC2H5)4 and organic solvent is C2H5OH. Add neodymium chloride hexahydrate and aluminum chloride hexahydrate to the mixed solution in sequence and stir well. Then, add silicon alkoxide hydrolysis catalyst HCl and adjust the pH value of the solution to the first pH value of 3. Stir well at room temperature for 10 hours to obtain Nd 3+ 、Al 3+ The co-doped silicon oxide transparent sol solution was allowed to stand for another 3 days; Step 3. Add the porous silica powder in batches in a fixed amount of 5 g each time to the vigorously stirred silica transparent sol solution, and continue stirring for 30 hours after the addition is completed to form a suspension; Step 4. Granulate the suspension by rotary evaporation to obtain a preliminary powder containing a certain amount of water and organic matter. Subsequently, place the preliminary powder in a tube furnace, slowly increase the temperature from 50°C to 1000°C at a rate of 1°C per minute in an oxygen atmosphere, and keep it at 1000°C for 8 hours to remove residual carbon and hydroxyl groups to form Nd-Al co-doped silica powder; Step 5. Use a ball mill to ball mill the silica powder to control the particle size to be less than 100 μm; Step 6: Place the ball-milled silica powder in a graphite crucible and place it in a high-temperature furnace at 1730°C for 10 -3 Melting is carried out for 4 hours under a torr vacuum, and bubble-free transparent glass is formed as the furnace cools; Step 7. Cold-process and polish the bubble-free transparent glass into a 2 mm sheet or an optical fiber core rod. The sheet glass is used for optical and spectral performance test and evaluation. The core rod is optically polished with a surface roughness of less than 10 nm. It is placed in HF acid with a mass concentration of 15% for acid treatment for 10 minutes, then taken out and dried for use as the core rod of Nd-Al co-doped quartz optical fiber.
[0040] Figure 4 The figure is a schematic diagram of the normalized absorption spectrum of Nd ions at room temperature based on the absorption peak at 580nm for the neodymium-doped quartz glass in the comparative example 1 and the exemplary example 2. The peak position of the absorption spectrum of Nd ions in the exemplary example 2 does not change significantly compared with the comparative example 1, especially at 808nm.
[0041] Figure 5 The figure is a schematic diagram of the normalized fluorescence spectrum (Ex=808nm) of Nd ions at room temperature based on the fluorescence sub-peak near 900nm in the neodymium-doped quartz glass in the comparative example 1 and the exemplary example 2. The fluorescence sub-peak near 900nm in the exemplary example 2 is shifted (blue shifted) 30nm to 870nm in the short-wave direction compared with the comparative example 1.
[0042] Embodiment 3: The components of the neodymium-doped quartz glass of this embodiment are: 0.05mol% Nd2O3, 1mol% P2O5, 98.95mol% SiO2, and its preparation method comprises the following steps: Step 1. Weigh the precursor raw materials of each component according to the selected molar percentage, the precursor raw material of P2O5 is phosphoric acid, the precursor raw material of Nd2O3 is neodymium chloride hexahydrate, 90wt% of the precursor raw material of SiO2 is porous silica powder, and 10wt% of the precursor raw material of SiO2 comes from silicon alkoxide; Step 2. Prepare a mixed solution in a volume ratio of silicon alkoxide: water: organic solvent = 1:6:12, wherein silicon alkoxide is Si(OC2H5)4 and organic solvent is C2H5OH. Add neodymium chloride hexahydrate and phosphoric acid to the mixed solution in sequence and stir well. Then, add silicon alkoxide hydrolysis catalyst HCl and adjust the pH value of the solution to a first pH value of 3. Stir well at room temperature for 10 hours to obtain Nd 3+ , P 5+ The co-doped silicon oxide transparent sol solution was allowed to stand for another 3 days; Step 3. Add the porous silica powder in batches at a fixed amount of 3 g each time to the vigorously stirred silica transparent sol solution, and continue stirring for 30 hours after the addition is completed to form a suspension; Step 4. Granulate the suspension by rotary evaporation to obtain a preliminary powder containing a certain amount of water and organic matter. Subsequently, place the preliminary powder in a tube furnace, slowly increase the temperature from 50°C to 1000°C at a rate of 1°C per minute in an oxygen atmosphere, and keep it at 1000°C for 10 hours to remove residual carbon and hydroxyl groups to form Nd-doped high-P silica powder; Step 5. Use a ball mill to ball mill the silica powder to control the particle size to be less than 100 μm; Step 6: Place the ball-milled silica powder in a graphite crucible and place it in a high-temperature furnace at 1730°C for 10 -3 Melting is carried out for 4 hours under a torr vacuum, and bubble-free transparent glass is formed as the furnace cools; Step 7. Cold process and polish the bubble-free transparent glass into 2 mm thick Nd-doped quartz sheet glass for optical and spectral performance testing and evaluation.
[0043] Embodiment 4: The components of the neodymium-doped quartz glass of this embodiment are: 0.8 mol% Nd2O3, 15 mol% P2O5, 84.2 mol% SiO2, and its preparation method comprises the following steps: Step 1. Weigh the precursor raw materials of each component according to the selected molar percentage, the precursor raw material of P2O5 is phosphoric acid, the precursor raw material of Nd2O3 is neodymium chloride hexahydrate, 92wt% of the precursor raw material of SiO2 is porous silica powder, and 8wt% of the precursor raw material of SiO2 comes from silicon alkoxide; Step 2. Prepare a mixed solution in a volume ratio of silicon alkoxide: water: organic solvent = 1:10:20, wherein silicon alkoxide is Si(OCH3)4 and organic solvent is CH3OH. Add neodymium chloride hexahydrate and phosphoric acid to the mixed solution in sequence and stir well. Then, add ammonia water as a catalyst for silicon alkoxide hydrolysis and adjust the pH value of the solution to a first pH value of 8. Stir well at room temperature for 10 hours to obtain Nd 3+ , P 5+ The co-doped silicon oxide transparent sol solution was allowed to stand for another 3 days; Step 3. Add the porous silica powder in batches in a fixed amount of 5 g each time to the vigorously stirred silica transparent sol solution, and continue stirring for 30 hours after the addition is completed to form a suspension; Step 4. Granulate the suspension by rotary evaporation to obtain a preliminary powder containing a certain amount of water and organic matter. Subsequently, place the preliminary powder in a tube furnace, slowly increase the temperature from 50°C to 1000°C at a rate of 1°C per minute in an oxygen atmosphere, and keep it at 1000°C for 8 hours to remove residual carbon and hydroxyl groups to form Nd-doped high-P silica powder; Step 5. Use a ball mill to ball mill the silica powder to control the particle size to be less than 100 μm; Step 6. Place the ball-milled silica powder in a graphite crucible and place it in a high-temperature furnace at 1500°C for 10 -3 The melting is carried out for 8 hours under a torr vacuum, and bubble-free transparent glass is formed as the furnace cools; Step 7. Cold process and polish the bubble-free transparent glass into 2 mm thick Nd-doped quartz sheet glass for optical and spectral performance testing and evaluation.
[0044] Embodiment 5: The components of the neodymium-doped quartz glass of this embodiment are: 0.4 mol% Nd2O3, 10 mol% P2O5, 89.6 mol% SiO2, and the preparation method thereof comprises the following steps: Step 1. Weigh the precursor raw materials of each component according to the selected molar percentage, the precursor raw material of P2O5 is phosphoric acid, the precursor raw material of Nd2O3 is neodymium chloride hexahydrate, 92wt% of the precursor raw material of SiO2 is porous silica powder, and 8wt% of the precursor raw material of SiO2 comes from silicon alkoxide; Step 2. Prepare a mixed solution in a volume ratio of silicon alkoxide: water: organic solvent = 1:10:20, wherein silicon alkoxide is Si(OCH3)4 and organic solvent is CH3OH. Add neodymium chloride hexahydrate and phosphoric acid to the mixed solution in sequence and stir well. Then, add silicon alkoxide hydrolysis catalyst HCl to adjust the pH value of the solution to a first pH value of 3. Stir well at room temperature for 10 hours to obtain Nd 3+ , P 5+ The co-doped silicon oxide transparent sol solution was allowed to stand for another 3 days; Step 3. Add the porous silica powder in batches in a fixed amount of 5 g each time to the vigorously stirred silica transparent sol solution, and continue stirring for 30 hours after the addition is completed to form a suspension; Step 4. Granulate the suspension by rotary evaporation to obtain a preliminary powder containing a certain amount of water and organic matter. Subsequently, place the preliminary powder in a tube furnace, slowly increase the temperature from 50°C to 1000°C at a rate of 1°C per minute in an oxygen atmosphere, and keep it at 1000°C for 8 hours to remove residual carbon and hydroxyl groups to form Nd-doped high-P silica powder; Step 5. Use a ball mill to ball mill the silica powder to control the particle size to be less than 100 μm; Step 6. Place the ball-milled silica powder in a graphite crucible and place it in a high-temperature furnace at 1500°C for 10 -3 The melting is carried out for 8 hours under a torr vacuum, and bubble-free transparent glass is formed as the furnace cools; Step 7. Cold process and polish the bubble-free transparent glass into 2 mm thick Nd-doped quartz sheet glass for optical and spectral performance testing and evaluation.
[0045] Embodiment 6: The components of the neodymium-doped quartz glass of this embodiment are: 0.6 mol% Nd2O3, 13 mol% P2O5, 86.4 mol% SiO2, and its preparation method comprises the following steps: Step 1. Weigh the precursor raw materials of each component according to the selected molar percentage, the precursor raw material of P2O5 is phosphoric acid, the precursor raw material of Nd2O3 is neodymium chloride hexahydrate, 90wt% of the precursor raw material of SiO2 is porous silica powder, and 10wt% of the precursor raw material of SiO2 comes from silicon alkoxide; Step 2. Prepare a mixed solution in a volume ratio of silicon alkoxide: water: organic solvent = 1:6:12, wherein silicon alkoxide is Si(OC2H5)4 and organic solvent is C2H5OH. Add neodymium chloride hexahydrate and phosphoric acid to the mixed solution in sequence and stir well. Then, add ammonia water as a catalyst for silicon alkoxide hydrolysis and adjust the pH value of the solution to a first pH value of 8. Stir well at room temperature for 10 hours to obtain Nd 3+ , P 5+ The co-doped silicon oxide transparent sol solution was allowed to stand for another 3 days; Step 3. Add the porous silica powder in batches at a fixed amount of 3 g each time to the vigorously stirred silica transparent sol solution, and continue stirring for 30 hours after the addition is completed to form a suspension; Step 4. Granulate the suspension by rotary evaporation to obtain a preliminary powder containing a certain amount of water and organic matter. Subsequently, place the preliminary powder in a tube furnace, slowly increase the temperature from 50°C to 1000°C at a rate of 1°C per minute in an oxygen atmosphere, and keep it at 1000°C for 10 hours to remove residual carbon and hydroxyl groups to form Nd-doped high-P silica powder; Step 5. Use a ball mill to ball mill the silica powder to control the particle size to be less than 100 μm; Step 6: Place the ball-milled silica powder in a graphite crucible and place it in a high-temperature furnace at 1730°C for 10 -3 Melting is carried out for 4 hours under a torr vacuum, and bubble-free transparent glass is formed as the furnace cools; Step 7. Cold process and polish the bubble-free transparent glass into 2 mm thick Nd-doped quartz sheet glass for optical and spectral performance testing and evaluation.
[0046] The sheet glasses of Examples 3 to 6 were tested in the same manner as in Example 1 and Example 2, and substantially the same test results as in Example 1 and Example 2 were obtained, that is, most of the Nd ions were present in the local microstructure of the P element, and the P element in the Nd-doped quartz glass was extremely uniformly distributed.
[0047] The neodymium-doped quartz glass with a fluorescence spectrum blue-shifted to the 870nm band and the preparation method thereof, by co-doping with phosphorus elements, accurately controls the local microstructure of Nd ions in the quartz glass, optimizes its coordination environment, thereby enhancing the coordination field, causing the energy level distribution of Nd ions to change, and successfully blue-shifts the fluorescence peak of the neodymium-doped quartz glass from 900nm to 870nm, effectively breaking through the limitation of the application of the 900nm band, providing strong technical support for the application of the 870nm band in the fields of biological imaging, quantum communication near-infrared light source and precision measurement, and further expanding the application prospects of Nd-doped quartz glass in the fields of high-power lasers and cutting-edge photonics.
[0048] The present invention has been described by the above-mentioned relevant embodiments, but the above-mentioned embodiments are only examples for implementing the present invention. In addition, the technical features involved in the different embodiments of the present invention described above can be combined with each other as long as they do not conflict with each other. It must be pointed out that the disclosed embodiments do not limit the scope of the present invention. On the contrary, changes and modifications made without departing from the spirit and scope of the present invention are all within the scope of patent protection of the present invention.
Claims
1. A method for preparing neodymium-doped quartz glass with a fluorescence spectrum blue-shifted to the 870nm band, characterized in that: The components of the neodymium-doped quartz glass include P2O5, Nd2O3 and SiO2, and the preparation method includes the following steps: Step 1. Weigh the precursor raw materials of each component according to the selected molar percentage, the precursor raw material of P2O5 is phosphoric acid, the precursor raw material of Nd2O3 is neodymium chloride hexahydrate, 90wt% to 95wt% of the precursor raw material of SiO2 is porous silica powder, and 5wt% to 10wt% of the precursor raw material of SiO2 comes from silicon alkoxide; Step 2. Prepare a mixed solution according to the volume ratio of silicon alkoxide: water: organic solvent = 1:2~10:4~20, then add neodymium chloride hexahydrate and phosphoric acid to the mixed solution in sequence, then add silicon alkoxide hydrolysis catalyst to adjust the pH value of the solution to the first pH value, and stir well at room temperature for 1 to 20 hours to obtain Nd 3+ , P 5+ The co-doped silicon oxide transparent sol solution is allowed to stand for 1 to 5 days; Step 3. Add the porous silica powder in batches according to a fixed addition amount to the vigorously stirred silica transparent sol solution for multiple times, and continue stirring for 2 to 48 hours after the addition is completed to form a suspension; Step 4. Granulate the suspension to obtain a preliminary powder, then heat the preliminary powder to 1000° C. in an oxygen atmosphere in a tube furnace and keep it at 1000° C. for 5 to 20 hours to remove residual carbon and hydroxyl groups to form Nd-doped high-phosphorus silica powder; Step 5. ball milling the silica powder using a ball mill and controlling the particle size to be below 100 μm; Step 6. Place the ball-milled silica powder in a graphite crucible and place in a high temperature furnace at 1500 to 1730°C for 10 -1 Up to 10 -3 The melting is carried out for 1 to 8 hours under a torr vacuum degree, and bubble-free transparent glass is formed along with furnace cooling. The bubble-free transparent glass is neodymium-doped quartz glass.
2. The method for preparing the neodymium-doped quartz glass with a fluorescence spectrum blue-shifted to the 870 nm band according to claim 1, characterized in that: The molar percentages of the components of the neodymium-doped quartz glass are: P2O5: 1 mol% to 15 mol%, Nd2O3: 0.05 mol% to 0.8 mol%, and the remaining components are SiO2.
3. The method for preparing the neodymium-doped quartz glass with a fluorescence spectrum blue-shifted to the 870 nm band according to claim 1, characterized in that: The median particle size of the porous silica powder is in the micro-nano order.
4. The method for preparing neodymium-doped quartz glass with a fluorescence spectrum blue-shifted to 870 nm as claimed in claim 1, characterized in that: The silicon alkoxide is Si(OC2H5)4 or Si(OCH3)4. When the silicon alkoxide is Si(OC2H5)4, the organic solvent is C2H5OH; when the silicon alkoxide is Si(OCH3)4, the organic solvent is CH3OH.
5. The method for preparing neodymium-doped quartz glass with a fluorescence spectrum blue-shifted to 870 nm as claimed in claim 1, characterized in that: The silicon alkoxide hydrolysis catalyst is hydrochloric acid or ammonia water. When the silicon alkoxide hydrolysis catalyst is hydrochloric acid, the first pH value is 1 to 3; when the silicon alkoxide hydrolysis catalyst is ammonia water, the first pH value is 8 to 10.
6. The method for preparing neodymium-doped quartz glass with a fluorescence spectrum blue-shifted to 870 nm as claimed in claim 1, characterized in that: In step 3, the fixed addition amount is 1 to 5 g each time.
7. The method for preparing neodymium-doped quartz glass with a fluorescence spectrum blue-shifted to 870 nm as claimed in claim 1, characterized in that: In step 4, the suspension is granulated by rotary evaporation.
8. A neodymium-doped quartz glass with a fluorescence spectrum blue-shifted to the 870nm band, characterized in that: The invention is prepared by the method for preparing neodymium-doped quartz glass with a fluorescence spectrum blue-shifted to the 870nm band as described in any one of claims 1 to 7.
9. A neodymium-doped silica optical fiber core rod, characterized in that: The invention is prepared from the neodymium-doped quartz glass with a fluorescence spectrum blue-shifted to the 870nm band as described in claim 8.
10. The Nd-doped silica optical fiber core rod according to claim 9, characterized in that: The Nd-doped quartz glass is cold processed and polished to obtain an optical fiber core rod, the surface roughness of the optical fiber core rod is less than 10nm, and the optical fiber core rod is placed in hydrofluoric acid with a mass concentration of 5 to 20% for acid treatment for 5 to 15 minutes, then taken out and dried to obtain the Nd-doped quartz optical fiber core rod.
Citation Information
Patent Citations
Preparation method of Nd3+ uniformly doped quartz glass
CN106396378A
Neodymium and ytterbium co-doped quartz laser glass and preparation method thereof
CN106495470A
Preparation technology for neodymium-doped quartz glass used for laser
CN108264217A
Preparation method of neodymium ion doped near-infrared microsphere laser
CN110649458A
Doped quartz glass and its production
JP1989076933A